2022
DOI: 10.1057/s41291-022-00209-y
|View full text |Cite
|
Sign up to set email alerts
|

Asian business and management: review and future directions

Abstract: This century has been proclaimed the Asian century, as industrialised countries such as Japan, Singapore, and South Korea, along with rapidly emerging nations such China and India, have contributed to worldwide economic growth. In response, research has analysed the reasons why Asian business and management have found such success. Based on a bibliometric analysis of Asian Business & Management (ABM), a premier journal devoted to Asian management, here we examine the performance of the research constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
(96 reference statements)
0
5
0
1
Order By: Relevance
“…Although prior research revealed that managerial ties are effective for improving the firm's performance and gaining competitive advantages (Wu and Chen, 2012;Wang et al, 2018) in many developed countries, studies on the effect of business ties on performance, especially in emerging economies, are quite limited (Chen and Wu, 2011;Sheng et al, 2011). Therefore, an increasing number of studies have been exploring the roles of business ties in management literature within the context of emerging economies recently (Froese et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior research revealed that managerial ties are effective for improving the firm's performance and gaining competitive advantages (Wu and Chen, 2012;Wang et al, 2018) in many developed countries, studies on the effect of business ties on performance, especially in emerging economies, are quite limited (Chen and Wu, 2011;Sheng et al, 2011). Therefore, an increasing number of studies have been exploring the roles of business ties in management literature within the context of emerging economies recently (Froese et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…, 2011). Therefore, an increasing number of studies have been exploring the roles of business ties in management literature within the context of emerging economies recently (Froese et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Managers build up informal relationships with their connections to develop potential partnerships, which are expected to lead to performance improvements, especially under uncertain environmental conditions (Mitrega and Pfajfar, 2015). Recently, business ties have gained prominence in emerging economies’ management literature (Froese et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In China, leadership research is among the most popular research areas in organizational behavior and management. Similarly, Chinese leadership research is a major stream in submissions to and publications in Asian Business & Management and other related scholarly journals (Froese et al, 2022 ). Considering these trends, Asian Business & Management features a focused issue on Chinese leadership in 2023.…”
Section: Introductionmentioning
confidence: 99%